The RNA-Binding Protein TIA-1 Is a Novel Mammalian Splicing Regulator Acting through Intron Sequences Adjacent to a 5′ Splice Site - Del Gatto-Konczak, Fabienne (American Society for Microbiology, 2000)
Splicing of the K-SAM alternative exon of the fibroblast growth factor receptor 2 gene is heavily dependent on the U-rich sequence IAS1 lying immediately downstream from its 5′ splice site. We show that IAS1 can activate the use of several heterologous 5′ splice sites in vitro. Addition of the RNA-binding protein TIA-1 to splicing extracts preferentially enhances the use of 5′ splice sites linked to IAS1. TIA-1 can provoke a switch to use of such sites on pre-mRNAs with competing 5′ splice sites, only one of which is adjacent to IAS1. Using a combination of UV cross-linking and specific immunoprecipitation steps, we show that TIA-1 binds to IAS1 in cell extracts. This binding is stronger if IAS1 is adjacent to a 5′ splice site and is U1 snRNP dependent. Overexpression of TIA-1 in cultured cells activates K-SAM exon splicing in an IAS1-dependent manner. If IAS1 is replaced with a bacteriophage MS2 operator, splicing of the K-SAM exon can no longer be activated by TIA-1. Splicing can, however, be activated by a TIA-1–MS2 coat protein fusion, provided that the operator is close to the 5′ splice site. Our results identify TIA-1 as a novel splicing regulator, which acts by binding to intron sequences immediately downstream from a 5′ splice site in a U1 snRNP-dependent fashion. TIA-1 is distantly related to the yeast U1 snRNP protein Nam8p, and the functional similarities between the two proteins are discussed.